Components of Cross-Frequency Modulation in Health and Disease - Allen, Elena A.; Liu, Jingyu; Kiehl, Kent A.; Gelernter, Joel; Pearlson, Godfrey D.; Perrone-Bizzozero, Nora I.; Calhoun, Vince D. (Frontiers in Systems Neuroscience, 2011)
The cognitive deficits associated with schizophrenia are commonly believed to arise from the abnormal temporal integration of information, however a quantitative approach to assess network coordination is lacking. Here, we propose to use cross-frequency modulation, the dependence of local high-frequency activity on the phase of widespread low-frequency oscillations, as an indicator of network coordination and functional integration. In an exploratory analysis based on pre-existing data, we measured cross-frequency modulation from multi-channel EEG recordings acquired while schizophrenia patients (n = 47) and healthy controls (n = 130) performed an auditory oddball task. Novel application of independent component analysis (ICA) to modulation data delineated components with specific spatial and spectral profiles, the weights of which showed co-variation with diagnosis. Global cross-frequency modulation was significantly greater in healthy controls (F1,175=9.25, P<0.005), while modulation at fronto-temporal electrodes was greater in patients (F1,175 =17.5, P<0.0001). We further found that the weights of schizophrenia-relevant components were associated with genetic polymorphisms at previously identified risk loci. Global cross-frequency modulation decreased with copies of 957C allele in the gene for the dopamine D2 receptor (r = −0.20, P < 0.01) across all subjects. Additionally, greater ‘aberrant’ fronto-temporal modulation in schizophrenia patients was correlated with several polymorphisms in the gene for the α2-subunit of the GABAA receptor (GABRA2) as well as the total number of risk alleles in GABRA2 (r = 0.45, P < 0.01). Overall, our results indicate great promise for this approach in establishing patterns of cross-frequency modulation in health and disease and elucidating the roles of oscillatory interactions in functional connectivity.